Analisis End-User Computing Satisfaction (EUCS) Dan WebQual 4.0 Terhadap Kepuasan Pengguna - T. Husain; Agus Budiyantara (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2018)
The world wide web is one of the most important aspects of the process of generating information aimed at the information society. The number of websites located in the domain ID .ac.id which is intended for college institutions serves as a media promotion and improvement of quality education services. The purpose of this study is to identify and measure the contribution of End-User Computing Satisfaction (EUCS) and WebQual 4.0 model consist of usability, information quality and services interaction dimension to user satisfaction on ABC Institution website. The research method used quantitative approach through structural equation modeling (SEM) analysis with confirmatory factor analysis technique. The results obtained from the analysis show that End-User Computing Satisfaction (EUCS) has a significant effect on User Satisfaction while the WebQual 4.0 model through usability and service interaction dimension has significant effect on User Satisfaction